Damage and failure modeling of lotus-type porous material subjected to low-cycle fatigue (Fracture and Structural Integrity, 2015)
The investigation of low-cycle fatigue behaviour of lotus-type porous material is presented in this paper. Porous materials exhibit some unique features which are useful for a number of various applications. This paper evaluates a numerical approach for determining of damage initiation and evolution of lotus-type porous material with computational simulations, where the considered computational models have different pore topology patterns. The low-cycle fatigue analysis was performed by using a damage evolution law. The damage state was calculated and updated based on the inelastic hysteresis energy for stabilized cycle. Degradation of the elastic stifness was modeled using scalar damage variable. In order to examine crack propagation path finite elements with severe damage were deleted and removed from the mesh during simulation. The direct cyclic analysis capability in Abaqus/Standard was used for low-cycle fatigue analysis to obtain the stabilized response of a model subjected to the periodic loading. The computational results show a qualitative understanding of pores topology influence on low-cycle fatigue under transversal loading conditions in relation to pore orientation.
Keywords: Porous materials; Low-cycle fatigue; Finite element analysis